2020
DOI: 10.1098/rsos.200650
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of mesoporous silicate molecular sieves by the aerosol-assisted method for loading and release of drug

Abstract: The mesoporous silicate molecular sieves were synthesized with polyether F127 as the template by the aerosol-assisted method for loading and release of ibuprofen (IBU). The synthesized samples were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction and N 2 adsorption–desorption isotherms. The drug IBU was applied as a model drug to investigate the drug release behaviour by ultraviolet spectrophotometry measurements. The investigation resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Solid acid has been used to replace the traditional acid catalyst in some chemical processes, 12 such as conversion of biomass, 13 hydrolysis of cellulose, 14 esterification, 15 alkylation, 16 and catalytic reduction. 17 The results showed that the catalytic activity of solid acid is largely depended on acid sites on the solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…Solid acid has been used to replace the traditional acid catalyst in some chemical processes, 12 such as conversion of biomass, 13 hydrolysis of cellulose, 14 esterification, 15 alkylation, 16 and catalytic reduction. 17 The results showed that the catalytic activity of solid acid is largely depended on acid sites on the solid surface.…”
Section: Introductionmentioning
confidence: 99%